PENGARUH UKURAN PERUSAHAAN DAN KEPEMILIKAN INSTITUSIONAL TERHADAP TAX AVOIDANCE DENGAN PROFITABILITAS SEBAGAI VARIABEL INTERVENING : STUDY PADA PERUSAHAAN MANUFAKTUR SEKTOR INDUSTRI DASAR DAN KIMIA DI BEI PERIODE 2016-2020 - Achmad Tjahjono; Yohanes Ambar Setyawan; Agung Slamet Prasetyo (Sekolah Tinggi Ilmu Ekonomi Widya Wiwaha, 2022)
This study aims to determine the effect of firm size and institutional ownership on tax avoidance with profitability as an intervening variable. The population of this research is all manufacturing companies in the basic and chemical industry sectors on the IDX for the 2016-2020 period. The sampling method used nonprobability sampling method with purposive sampling technique. The data analysis technique used the classical assumption test, namely the multicollinearity test, autocorrelation test, heteroscedasticity test and normality test. Hypothesis testing using path analysis (path analysis). The results of the study conclude that: (1) Firm size has a positive and significant effect on profitability, (2) institutional ownership has a positive and significant effect on profitability, (3) Profitability has a positive effect and significant to tax avoidance as measured by the effective tax rate, (4) Company size has a positive and significant effect on tax avoidance as measured by the effective tax rate, (5) Institutional ownership has a positive and significant effect on tax avoidance as measured by the effective tax rate, (6) Profitability is not able to provide a significant influence between firm size and tax avoidance, (7) Profitability is not able to provide a significant influence between institutional ownership and tax avoidance.